Hubungan Kuantitatif Struktur Elektronik . Aktivitas Senyawa Antimalaria Turunan Artemisinin Dengan PendekatanRegresi Komponen Utama - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Analysis of quantitative structure - activity relationship (QSAR) for a series of antimalarial compound artemisinin derivatives has been done using principal component regression. The descriptors for QSAR study were representation of electronic structure i.e. atomic net charges of the artemisinin skeleton calculated by AM1 semiempirical method. The antimalarial activity of the compound was expressed in log 1/1Csowhich is an experimental data. The main purpose of the principal component analysis approach is to transform a large data set of atomic net charges to simplify into a data set which known as latent variables. The best QSAR equation to analyze of log 1/ICso can be obtained from the regression method as a linear function of several latent variables i.e. X1,X2,X3,X4and Xs. Thebest QSAR model is expressed in the following equation, log111Cso = -28,29+ 2,19x1 - 21,39x2 - 35,71x3 + 57,8x4 - 8,36xs(n =33